Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1004
|View full text |Cite
|
Sign up to set email alerts
|

It’s going to be okay: Measuring Access to Support in Online Communities

Abstract: People use online platforms to seek out support for their informational and emotional needs. Here, we ask what effect does revealing one's gender have on receiving support. To answer this, we create (i) a new dataset and method for identifying supportive replies and (ii) new methods for inferring gender from text and name. We apply these methods to create a new massive corpus of 102M online interactions with gender-labeled users, each rated by degree of supportiveness. Our analysis shows widespread and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 72 publications
(49 reference statements)
1
36
0
Order By: Relevance
“…1 Second, it varies in both content and tone. Third, users can develop strong identities on the site, which could facilitate user-level modeling, but these identities are generally pseudonymous, which is useful when studying charged social phenomena Wang and Jurgens, 2018). Fourth, the subreddit structure of the site creates opportunities to study the impact of condescension on community structure and norms (Buntain and Golbeck, 2014;Lin et al, 2017;Chandrasekharan et al, 2018).…”
Section: The Talkdown Corpusmentioning
confidence: 99%
“…1 Second, it varies in both content and tone. Third, users can develop strong identities on the site, which could facilitate user-level modeling, but these identities are generally pseudonymous, which is useful when studying charged social phenomena Wang and Jurgens, 2018). Fourth, the subreddit structure of the site creates opportunities to study the impact of condescension on community structure and norms (Buntain and Golbeck, 2014;Lin et al, 2017;Chandrasekharan et al, 2018).…”
Section: The Talkdown Corpusmentioning
confidence: 99%
“…There have been a few other computational studies that predict the effects of online self-presentation. Wang and Jurgens [37] examined how the presentation of gender on Reddit, StackExchange, and Wikipedia affects reactions of support. Bareket-Bojmel et al [5] examined how self-enhancing and self-derogating posting strategies affected responses to users with different goals on Facebook.…”
Section: Identity and Interactionmentioning
confidence: 99%
“…Other studies have looked at the effect of suicide prevention counselor training (Gould et al, 2013), identifying patterns of successful crisis hotline counselors (Althoff et al, 2016), automating counselor evaluation (Pérez-Rosas et al, 2017), and building a dashboard for crisis counselors (Dinakar et al, 2015). There is additional work to identify supportive and distressed behaviors and language in online forums (Balani and De Choudhury, 2015;De Choudhury and De, 2014;Wang and Jurgens, 2018) and support forum moderators (Hussain et al, 2015). Most similar to our study, was one study that showed the potential for an avatar system to help train medical doctors to deliver news to patients (Andrade et al, 2010).…”
Section: Related Workmentioning
confidence: 99%